Is unintended birth associated with physical intimate partner violence? Evidence from India. Issue 6 (6th November 2020) - Goli, Srinivas; Gautam, Abhishek; Rana, Md Juel; Ram, Harchand; Ganguly, Dibyasree; Reja, Tamal; Nanda, Priya; Datta, Nitin; Verma, Ravi
Abstract: A growing number of studies have tested the association between intimate partner violence (IPV) and the unintendedness of pregnancy or birth, and most have suggested that unintendedness of pregnancy is a cause of IPV. However, about nine in every ten women face violence after delivering their first baby. This study examined the effects of the intendedness of births on physical IPV using data from the National Family Health Survey (2015–16). The multivariate logistic regression model analysis found that, compared with women with no unwanted births (2.9%), physical IPV was higher among those women who had unwanted births (6.9%, p <0.001), followed by those who had mistimed births (4.4 %, p <0.001), even after adjusting for several women's individual and socioeconomic characteristics. Thus, the reduction of women with mistimed and unwanted births could reduce physical IPV in India. The study highlights the unfinished agenda of family planning in the country and argues for the need to integrate family planning and Reproductive, Maternal and Child Health Care (RMNCH) services to yield multi-sectoral outcomes, including the elimination of IPV.